The effects of cooperative learning on writing skills in PINE major students. - Córdova Lituma, Emily Scarlet (2023)
Writing proficiency among English-speaking students, particularly in the seventh semester of the Major in Pedagogía de los Idiomas Nacionales y Extranjeros, is crucial. So, they express their ideas and thoughts clearly and coherently. This proficiency is essential for effective communication in various contexts; academic, professional, and personal settings. Moreover, implementing the Cooperative learning method in the writing process is fundamental for students to develop their writing skills, as it allows them to support and learn from their peers through knowledge sharing. This research project aims to recognize the effectiveness of the cooperative learning method on the writing skills of PINE Major Students. Consequently, the main objective of this research project is to analyses the effect of Cooperative learning method on writing skills in PINE Major Students. To achieve this, the researchers employed a qualitative focus conducting interviews with teachers to gather their opinions on the cooperative learning method. To further explore this research project, we organized a focus group with students to evaluate their proficiency in English writing skills.